A clickable photoaffinity probe of betulinic acid identifies tropomyosin as a target - Pedro Martín-Acosta; Qianli Meng; John Klimek; Ashok P. Reddy; Larry David; Stefanie Kaech Petrie; Bingbing X. Li; Xiangshu Xiao (Elsevier, 2022)
Target identification of bioactive compounds is important for understanding their mechanisms of action and provides critical insights into their therapeutic utility. While it remains a challenge, unbiased chemoproteomics strategy using clickable photoaffinity probes is a useful and validated approach for target identification. One major limitation of this approach is the efficient synthesis of appropriately substituted clickable photoaffinity probes. Herein, we describe an efficient and consistent method to prepare such probes. We further employed this method to prepare a highly stereo-congested probe based on naturally occurring triterpenoid betulinic acid. With this photoaffinity probe, we identified tropomyosin as a novel target for betulinic acid that can account for the unique biological phenotype on cellular cytoskeleton induced by betulinic acid.